Sequence analysis of the polymerase 1 gene and the secondary structure prediction of polymerase 1 protein of human influenza virus A/WSN/33. - Sivasubramanian, N (1982)
The nucleotide sequence of polymerase 1 (P1) gene of a human influenza virus (A/WSN/33) has been determined by using cDNA clones, except for the last 83 nucleotides, which were obtained by primer extension. The WSN P1 gene contains 2,341 nucleotides and codes for a protein of 757 amino acids (Mr = 86,500). P1 gene possesses a striking tandem repeat of 12 nucleotides (nucleotide position 2,188 to 2,199, 2,200 to 2,211) and a corresponding tandem repeat of tetrapeptide in the P1 protein. The deduced sequence of P1 protein is enriched in basic amino acids, particularly arginine. In addition, it also contains clusters of basic amino acids which may provide sites for the interaction with the template virion RNA capped primer as well as with other proteins involved in viral replication and transcription. A secondary structure prediction, using Chou and Fasman analyses (Annu. Rev. Biochem. 47:251-276, 1978), shows that the P1 protein possesses some unique features, viz., one "four-helical supersecondary structure" and four "polypeptide double helices" (antiparallel beta-pleated sheets) which are considered important in RNA binding.